Spelling Changes and Fluorescent Tagging With Prime Editing Vectors for Plants - Wang, Li; Kaya, Hilal Betul; Zhang, Ning; Rai, Rhitu; Willmann, Matthew R.; Carpenter, Sara C. D.; Read, Andrew C.; Martin, Federico; Fei, Zhangjun; Leach, Jan E.; Martin, Gregory B.; Bogdanove, Adam J. (Frontiers in Genome Editing, 2021)
Prime editing is an adaptation of the CRISPR-Cas system that uses a Cas9(H840A)-reverse transcriptase fusion and a guide RNA amended with template and primer binding site sequences to achieve RNA-templated conversion of the target DNA, allowing specified substitutions, insertions, and deletions. In the first report of prime editing in plants, a variety of edits in rice and wheat were described, including insertions up to 15 bp. Several studies in rice quickly followed, but none reported a larger insertion. Here, we report easy-to-use vectors for prime editing in dicots as well as monocots, their validation in Nicotiana benthamiana, rice and Arabidopsis, and an insertion of 66 bp that enabled split-GFP fluorescent tagging.